An Integral Involving Generalized Hypergeometric Function - Basnet, Ganesh Bahadur; Pahari, Narayan Prasad; Paudel, Resham Prasad; Poudel, Madhav Prasad; Sharma, Mukesh (Nepal Journal of Mathematical Sciences, 2024)
In this article, we have evaluated an integral involving a generalized hypergeometric function. This is achieved by employing a summation formula for the series 4F3 obtained earlier by Choi and Rathie [3]. A few special cases have also been given. The result provided in this note is simple, interesting, easily established, and may be useful. 2020 Mathematical subject classification: Primary: 05A15, 33C05, Secondary: 33C15, 33C20